A Feminist Peep into Public Art in India's Northeast. Issue 1 (June 2017) - Barooah, Samhita
Based on participant observation, symbolic interactionism and feminist analysis of diverse art forms available in the public domain, the article focuses on the stereotyped notion of masculinity, which gets projected into the urban landscape of modern cities in Northeast India. It takes a critical stance on some of the prominent mascots, symbols and identities which are attached to products, services and ideologies predominantly rooted in patriarchy and gender-based discrimination. The observations shared in the article are drawn from the researcher's field experiences and do not hold any offence to any particular agency, group, denomination or individual. It attempts to bring forth a subaltern narrative which is gradually getting erased from public memory from a queer feminist lens of locating oneself in a public space. It also questions the gender-normative imagination of modern India, which is rapidly engulfing all forms of diversity into its monoculture of development.